Beyond Crisis: Discernment in Decision-making for Sustainable Church Health - Hardiyan Triasmoroadi (Journal of Ethics in Higher Education)
This study explores the integration of discernment into the decision-making framework. Focusing on the financial crisis within the East Java Christian Church, which led to opposition, distrust, and the collapse of peace within the Church, it identifies a disconnection between decision-making and spiritual awareness. By examining social discernment, Ignatian discernment, and contemplative artistic practice, the researcher proposes practical steps for implementation. Ultimately, this essay advocates for a comprehensive approach to discernment that not only addresses immediate crisis but also lays the groundwork for sustainable institutional health, trust, and peace within church communities.